Analysis Of The Content Of The Mother Language Curriculum - Olimov, Temir Hasanovich; Kadirova, Mahbuba Odilovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This thesis analyzes the content structure of the mother tongue curriculum. The study examines the main goals and objectives of the curriculum, its role in the educational process, the distribution of topics across grades, and their sequence and logical coherence. The thesis also discusses the curriculum sections, including phonetics, lexicology, grammar, word formation, and speech development. The work emphasizes the importance of combining theoretical knowledge with practical application and highlights the role of exercises and assignments in developing students’ independent and critical thinking skills. It evaluates the level of oral and written language skills formation in students based on the competency-based approach reflected in the mother tongue curriculum. In addition, the alignment of the curriculum with state educational standards and the regulatory documents approved by the Oʻzbekiston Respublikasi Maktabgacha va maktab taʼlimi vazirligi is analyzed. The study identifies the strengths and weaknesses of the curriculum and provides recommendations for its further improvement. The results of this thesis aim to enhance the quality of mother tongue education, organize the learning process effectively, strengthen students’ language knowledge, and increase their interest in the native language.